2020
DOI: 10.21203/rs.3.rs-51667/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Corticosteroids and Immunosuppressive Therapies on Symptomatic SARS-CoV-2 Infection in a Large Cohort of Patients with Chronic Inflammatory Arthritis

Abstract: Background: Prevalence and outcomes of Coronavirus Disease (COVID)-19 in relation to immunomodulatory medications are still unknown. The aim of the study is to investigate the impact of glucocorticoids and immunosuppressive agents on COVID-19 in a large cohort of patients with chronic immune-mediated inflammatory arthritis.Methods: The study was conducted in the arthritis outpatient clinic at two large Academic Hospitals in the COVID-19 most endemic area of Northern Italy (Lombardy). We circulated a cross-sect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
(68 reference statements)
1
3
0
Order By: Relevance
“…Similarly, our data showed a risk of COVID-19 increased in chronic GCs users at dose > 2.5 mg daily (OR 4.22, 95% CI 1.74-10.23) [31]. Finally, a comprehensive meta-analysis of 62 observational studies including 319,025 patients with autoimmune diseases from 15 countries showed that GCs use prior to COVID-19 significantly contributed to the disease prevalence; meanwhile, therapies including csDMARDs and b/tsDMARDs did not contribute to the risk of COVID-19.…”
Section: Do Immunosuppressive/immunomodulatory Anti-rheumatic Drugs Isupporting
confidence: 81%
See 1 more Smart Citation
“…Similarly, our data showed a risk of COVID-19 increased in chronic GCs users at dose > 2.5 mg daily (OR 4.22, 95% CI 1.74-10.23) [31]. Finally, a comprehensive meta-analysis of 62 observational studies including 319,025 patients with autoimmune diseases from 15 countries showed that GCs use prior to COVID-19 significantly contributed to the disease prevalence; meanwhile, therapies including csDMARDs and b/tsDMARDs did not contribute to the risk of COVID-19.…”
Section: Do Immunosuppressive/immunomodulatory Anti-rheumatic Drugs Isupporting
confidence: 81%
“…Another survey-based study conducted by our group in a cohort of 2050 patients with chronic inflammatory arthritis showed a decreased risk in b/tsDMARDs users (OR 0.47, 95% CI 0.46-0.48) while csDMARDs did not modify the odds of infection [31]. On a Spanish cohort of 123 patients with autoimmune inflammatory rheumatic disease and COVID-19, 54 patients required hospital admission related to COVID-19; patients exposed to DMARDs were not at higher risk of hospitalization, and those treated with anti-TNF had a statistically significant lower risk (OR 0.13, 95% CI 0.03-0.63) [32].…”
Section: Do Immunosuppressive/immunomodulatory Anti-rheumatic Drugs Imentioning
confidence: 73%
“…Whether or not patients with systemic GC treatment are at an increased risk of SARS-CoV-2 infection and/ or severe outcomes is so far not fully clarified. On the one hand, GCs were discussed theoretically to mitigate hyperimmune reactions responsible for severe disease progression [26]. An enhanced local innate immune defense in respiratory epithelial cells was reported in response to GC exposure, beside the known anti-inflammatory and anti-allergic actions of GCs [27].…”
Section: Risk In Exogenous Glucocorticoid Excessmentioning
confidence: 99%
“…Due to the heterogeneous studies with different sample sizes, variable diseases included, diagnostic criteria and geographic location, these data should be interpreted with caution. However, there are other studies of patients with autoimmune or inflammatory diseases and GC exposure that have described an increased risk of SARS-CoV-2 infection [26,29,30]. Table 1 shows studies with patients under GC treatment and SARS-CoV-2 infection.…”
Section: Risk In Exogenous Glucocorticoid Excessmentioning
confidence: 99%